2008
DOI: 10.1021/ef800031x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atmospheric Residue Incorporation in the Fluidized Catalytic Cracking (FCC) Feed on Product Stream Yields and Composition

Abstract: A study has been carried out on the cracking of a mixture of atmospheric residue (20 wt %) and VGO (vacuum gas-oil) from a refinery, in a riser simulator reactor under industrial unit conditions in the 525-575 °C range, with contact times between 3 and 12 s and using a commercial catalyst for residues. The yields and compositions of the product streams (dry gas, LPG, gasoline, LCO, HCO, and coke) have been compared to those corresponding to a standard feed in a fluidized catalytic cracking (FCC) unit. Catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…It is worth mentioning that the variables describing process conditions and catalyst properties have very low impact, expressed as low loadings along PC1. The critical role of feed composition on the overall performance of the FCC process has been recurrently indicated before [12,24,28,55]. Based on their loadings (highest and lowest along PC1), the distribution of boiling point fractions of the feed (Hf, Gf or Lf) has a stronger impact on process performance than its chemical composition (Pf, Of, Af or Nf).…”
Section: Multivariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the variables describing process conditions and catalyst properties have very low impact, expressed as low loadings along PC1. The critical role of feed composition on the overall performance of the FCC process has been recurrently indicated before [12,24,28,55]. Based on their loadings (highest and lowest along PC1), the distribution of boiling point fractions of the feed (Hf, Gf or Lf) has a stronger impact on process performance than its chemical composition (Pf, Of, Af or Nf).…”
Section: Multivariate Analysismentioning
confidence: 99%
“…However, taking the remarkable versatility of FCC, other non-conventional feeds have also been studied [10]: (i) secondary refinery streams; (ii) streams derived from the consumer society; or (iii) oxygenated bio-derived feedstock. As secondary refinery streams (i), Arandes et al [11,12] studied the effect of co-feeding atmospheric distillation residue (20 wt %) with VGO in a riser simulator, observing a crucial role of the reactant accessibility for the Processes 2018, 6, 243 2 of 15 efficient conversion of bulky aromatic molecules, and also the great influence of the temperature and catalyst/oil (C/O) ratio on gasoline composition. Garcia et al [13] observed an improvement of conversion of the blend of atmospheric distillation residue (10 wt %) and VGO, compared with the VGO alone.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the variables describing process conditions and catalyst properties have very low impact, expressed as low loadings along PC1. The critical role of feed composition on the overall performance of the FCC process has been recurrently indicated before [12,24,28,53].…”
Section: Multivariate Analysismentioning
confidence: 99%
“…However, taking the remarkable versatility of FCC, other non-conventional feeds have been studied [10]: (i) secondary refinery streams, (ii) streams derived from the consumer society, or (iii) oxygenated bio-derived feedstock. As secondary refinery streams (i), Arandes et al [11,12] studied the effect of co-feeding atmospheric distillation residue (20 wt%) with VGO in a riser simulator, observing a crucial role of the reactant accessibility for the efficient conversion of bulky aromatic molecules, and also the great influence of the temperature and catalyst/oil (C/O) ratio on gasoline composition. Garcia et al [13] observed an improvement of conversion of the blend of atmospheric distillation residue (10 wt%) and VGO, compared with the VGO alone.…”
Section: Introductionmentioning
confidence: 99%
“…A real‐time prediction model for product properties and output variables of the FCC and RFCC processes is important in order to propose process changes and to deal with a large amount of process data. Mathematical models of the product properties of FCC and RFCC processes have been proposed . However, such approaches have limitations.…”
Section: Introductionmentioning
confidence: 99%